Electrochemical Measurement of Sieverts' Constant and Solubility of Oxygen in LBE at 598–748 K. Issue 12 (1st January 2017) - Lim, Jun; Gabriele, Manfredi; Marino, Alessandro; Gladinez, Kristof; Aerts, Alexander
Abstract : The solubility of oxygen in liquid lead bismuth eutectic (LBE) was determined by using electrochemical methods. The oxygen partial pressure in oxygen saturated LBE was measured from 475 to 724 K by using an oxygen sensor comprised of yttria partially stabilized zirconia and air/LSM (Lanthanum strontium manganite) reference electrode. Sieverts' constant of the dissolved oxygen in LBE was measured from 598 to 748 K by coulometric titration method using the oxygen sensor. The measured oxygen partial pressure in oxygen saturated LBE (P O 2 ( L B E − P b O ) in bar) and Sieverts' constant of dissolved oxygen in LBE ( k for a 1 wt% standard state) are given by log P O 2 ( L B E − P b O ) = 11.52 − 22996 / T (475–724 K), log  k = 3.12 − 7072/ T (598–748 K) respectively. Combining the measured data, the oxygen solubility in LBE ( C O, S in wt%) was derived and is given by log  C O, S = 2.64 − 4426/ T (598–724 K).